Determinant of Utilization and Perceived Health Benefits of Indigenous Foods (NDIISE) Among Households in Akwa Ibom State, Nigeria - Idara Etim Ituen (INTERNATIONAL JOURNAL OF AGRICULTURE AND EARTH SCIENCE, 2026)
This study investigated the determinants of utilization and perceived health benefits of indigenous foods (locally known as Ndiise) among 432 randomly selected households in Akwa Ibom State, Nigeria, using a community‑based cross‑sectional design. A validated questionnaire captured socio‑demographic characteristics, consumption frequency of 16 indigenous foods (seven‑day recall), health benefit awareness (10‑item Likert scale), and perceived constraints. A composite utilization score (0–100) was constructed. Data were analyzed using descriptive statistics, Pearson correlation, and multiple linear regression. The mean utilization score was 45.2 ± 21.6, with 32.9% of households showing low, 43.5% moderate, and 23.6% high utilization. The mean health awareness score was 48.6 ± 18.4, and awareness was positively correlated with utilization (r = 0.482, p < 0.001). Regression analysis (R² = 0.486) identified health benefit awareness (β = 0.412), rural residence (β = 0.276), education (β = 0.198), farm ownership (β = 0.182), age (β = 0.168), cooperative membership (β = 0.128), and market distance (β = –0.164) as significant predictors. Major constraints were seasonal availability (66.4%), time‑intensive preparation (56.3%), and children's preferences (49.5%). The study recommends enhancing awareness, promoting home gardens, and strengthening local food systems as critical strategies to sustain indigenous food utilization.